Studi Rasionalitas Pemakaian Obat Antihipertensi Pada Kasus Pasien Rawat Jalan - Endah Nurrohwinta Djuwarno; Faramita Hiola; Fika Nuzul Ramadhani; Divia Handayani Mudjidu; Teti Sutriati Tuloli (Journal Syifa Sciences and Clinical Research, 2022)
Hypertension is a disease that happens when the systolic and diastolic blood pressure is higher than 140/90 mmHg. This study aimed to identify the use of an anti-hypertension drug on outpatients at Kota Timur Community Health Center in Gorontalo, with medical records of hypertension patients from January to June 2021 as the data source. Employing the univariate analysis method, this study obtained patients' data to be recapitulated into the primary table to be descriptively analyzed. The findings in gender frequency revealed that 36 male respondents attained 53.3% of percentage and 81 female respondents attained 46.6% of percentage, while the respondent age frequency that is mostly 46-65 years old numbered 83 patients (71%), 26-45 years old numbered 22 patients (18.80%), and 65 years old numbered 12 patients (10.25%). Based on drug use from January to June 2021, the most consumed drug is Amlodipine, with 70 consumption (60%). Further, based on diseases in other categories from January to June 2021, the highest diagnosis on hypertension patients is 71 times of hypertension (60%), while the systolic and diastolic pressure category from January to June 2021 revealed that the highest blood pressure of the stage 1hypertension patients is 63 times (54%).